(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Experimental and numerical study of fluid flow and heat transfer in microchannel airflow is investigated. The study covers changing the cooling of micro-channel for the velocities and heater powers. The dimensions of the microchannel were, length = 0.1m, width = 0.001m, height = 0.0005 m. The experimental and numerical results were compared with the previous paper for velocities up to 20 m/s and heater powers up to 5 W and the comparison was acceptable. In this paper, the results were extended numerically for velocities up to 60 m/s. The numerical solution used finite volume (SIMPLE algorithm) to solve Navier Stokes equations (continuity, momentum and energy). The results show that the heat transfer coefficient increases up to 220 W/m2 oC for velocity 60 m/s.